External Parasites on Horses - Phillip E. Kaufman; Philip G. Koehler; Jerry F. Butler (EDIS, 2006)
Arthropod parasites of horses include internal bots that infest the digestive tract, mites that burrow in the skin and feed on the skin surface, ticks that infest the ears as well as the skin, lice that either suck blood or feed on skin, blood sucking flies and mosquitoes that range in size from biting gnats just observable with the naked eye to the large black horse flies which are almost one inch long. Non-biting flies such as house flies and face flies are also important in producing fly worry, irritation and disease transmission. This document is ENY-283 (IG139), one of a series of the Entomology and Nematology Department, UF/IFAS Extension. Original publication date May 1980. Revised March 2006.